Retail price differences across U.S. and Canadian cities during the interwar period - Chris Hajzler; James MacGee (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2015)
We construct a unique panel of retail food prices in 69 Canadian and 51 U.S. cities during the Interwar (1920-40) period. Surprisingly, we find that average relative price dispersion across cities within Canada and the U.S., and the role of distance in accounting for cross-city price differences, was very similar to estimates from the 1980s and 1990s. We also find large changes in the importance of the Canada- U.S. border during the Interwar period. While increased price differences between Canadian and U.S. cities coincide with the end of the gold-standard (and the move to floating nominal exchange rates), large relative and absolute price differences persist even after the Canada-U.S. nominal exchange rate returned to parity. The substantial "thickening" of the border in the 1930s appears to reflect dramatic changes in trade policy and the degree of market integration during this period.
Keywords: E31; 330; Law of One Price; Relative Prices